PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN LIKUIDITAS TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR CONSUMER GOODS DI BURSA EFEK INDONESIA - Ardityawati, Ni Putu Lisna; Candraningrat, Ica Rika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023, 2023)
Stock return is the profit obtained by companies, individuals, and institutions from the results of their investment policies. Before investing in the capital market, especially in the stock market, investors need to collect information about the company's fundamental conditions to get return investment in the long-term. The purpose of this study was to determine the effect of capital structure, profitability and liquidity on stock return. This research was conducted at consumer goods sector companies that are listed on the Indonesia Stock Exchange for the 2017-2020 period. The data used in this study is quantitative data with secondary data sources published by the Indonesia Stock Exchange. The sample used in this study were 34 companies through purposive sampling method. This study used non-participant observation method. The analysis technique used is multiple linear regression. Based on the results of the analysis found that the debt to equity ratio had a negative and insignificant effect on stock return, return on assets had a positive and significant effect on stock return and current ratio had a positive and insignificant effect on stock return. Investors and company management are expected to pay more attention to return on asset that have an impact on stock return .